MEMORY AS DISCOURSE IN HAROLD PINTER’S «OLD TIMES» , «BETRAYAL» AND «A KIND OF ALASKA» - Castro, Carla Ferreira de (POLISSEMA – Revista de Letras do ISCAP, 2019)
This paper aims at developing the topic of identity and the narration of the self through the other in Harold Pinter’s plays Old Times, Betrayal and A Kind of Alaska. In these plays Pinter deploys strategies to convey multiple implications which are based on the power of memory in which the structure of the plays is concocted.